The Impact of the Health Belief Model Booklet Intervention on Behavior about Preventing High Risk of Pregnancy - Teresia Retna Puspitadewi; Wahyuningsih Triana Nugraheni (Humanistic Network for Science and Technology (HNST), 2020)
Every pregnant woman has the risk of experiencing childbirth complications with various impacts including death, morbidity, disability. The objective of this study is to determine the impact of the health belief model booklet-based intervention on the prevention of high-risk pregnancy behavior in Merak Urak District, Tuban Regency. This type of research was a quasi experimental study using a post test with control group design, to determine the effect of an intervention using the Health Belief Model based booklet on prevention of high risk pregnancy behavior. The subjects in this study were all 60 pregnant women in the District of Merak Urak, Tuban Regency, selected by cluster sampling. Data were collected using an instrument in the form of a questionnaire, then analyzed by Manova test. Keywords: health belief model; booklet; health education; high-risk pregnancy